2014
DOI: 10.1152/ajpcell.00293.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis transmembrane conductance regulator dysfunction in VIP knockout mice

Abstract: Vasoactive intestinal peptide (VIP), a neuropeptide, controls multiple functions in exocrine tissues, including inflammation, and relaxation of airway and vascular smooth muscles, and regulates CFTR-dependent secretion, which contributes to mucus hydration and local innate defense of the lung. We had previously reported that VIP stimulates the VPAC1 receptor, PKCϵ signaling cascade, and increases CFTR stability and function at the apical membrane of airway epithelial cells by reducing its internalization rate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Previous human studies have shown that the rich intrinsic neuronal networks for VIP secretion around exocrine glands could be lost in tissues from patients with cystic fibrosis. Our research has since confirmed, in vitro and in vivo , the need for chronic VIP exposure to maintain functional CFTR chloride channels at the cell surface of airways and intestinal epithelium, as well as normal exocrine tissues morphology [1] . The goal of the present study was to examine changes in VIP in the lung, duodenum and sweat glands of 8-and 17-weeks old F508del/F508del mice and to investigate VIPergic innervation in the small intestine of CF mice, before important signs of the disease development.…”
supporting
confidence: 53%
“…Previous human studies have shown that the rich intrinsic neuronal networks for VIP secretion around exocrine glands could be lost in tissues from patients with cystic fibrosis. Our research has since confirmed, in vitro and in vivo , the need for chronic VIP exposure to maintain functional CFTR chloride channels at the cell surface of airways and intestinal epithelium, as well as normal exocrine tissues morphology [1] . The goal of the present study was to examine changes in VIP in the lung, duodenum and sweat glands of 8-and 17-weeks old F508del/F508del mice and to investigate VIPergic innervation in the small intestine of CF mice, before important signs of the disease development.…”
supporting
confidence: 53%
“…It is well known to work in synergy with ACh to regulate secretions (Lundberg et al, 1980; Heinz-Erian et al, 1985, 1986). Interestingly, VIP KO mice generated in the C57BL/6 background demonstrated, in vivo , the central role of VIP in CFTR regulation (Chappe and Said, 2012; Alcolado et al, 2014). Originally developed to study airway diseases, such as bronchial asthma (Hamidi et al, 2006; Szema et al, 2006; Said, 2009), VIP-KO mice were used by Alcolado et al (2014) to demonstrate the molecular link between VIP and CFTR regulation in the airways and small intestines, and observed a CF-like phenotype.…”
Section: Murine Models In Cystic Fibrosis Researchmentioning
confidence: 99%
“…In addition, the maximal venodilatation achieved was less in CF patients [54]. The apparent increase in smooth muscle thickness is also seen in VIP knock-out mice both in the lung and the intestine [55], together with interference with CFTR localisation.…”
Section: Evidence For Changes In Intestinal and Vascular Smooth Musclmentioning
confidence: 95%